求解有分数的完全平方

职业培训 培训职业 2024-12-07
3X^2+10X+3=10 3X^2+10X+3-10=0 3X^2+10X-7=0 X1=(-10+(10^2+4*3*7)^0.5)/(2*3) =(-10+(100+84)^0.5)/6 =(-10+(184^0.5))/6 =(-10+2*(46^0.5))/6 =(-5+(46^0.5))/3 X2=(-10-(10^2+4*3*7)^0.5)/(2*3) =(-10-(100+84)^0.5)/6 =(-10-(184^0.5))/6 =(-10-2*(46^0.5))/6 =(-5-(46^

3X^2+10X+3=10

3X^2+10X+3-10=0

3X^2+10X-7=0

X1=(-10+(10^2+4*3*7)^0.5)/(2*3)

=(-10+(100+84)^0.5)/6

=(-10+(184^0.5))/6

=(-10+2*(46^0.5))/6

=(-5+(46^0.5))/3

X2=(-10-(10^2+4*3*7)^0.5)/(2*3)

=(-10-(100+84)^0.5)/6

=(-10-(184^0.5))/6

=(-10-2*(46^0.5))/6

=(-5-(46^0.5))/3

标签

版权声明:本文由哟品培原创或收集发布,如需转载请注明出处。

本文链接:http://www.yopinpei.com/20241207/2/413901

猜你喜欢
其他标签